SARS‐CoV‐2‐reactive antibody detection after SARS‐CoV‐2 vaccination in hematopoietic stem cell transplant recipients: Prospective survey from the Spanish Hematopoietic Stem Cell Transplantation and Cell Therapy Group. Issue 1 (2nd November 2021) - Piñana, José Luis; López‐Corral, Lucia; Martino, Rodrigo; Montoro, Juan; Vazquez, Lourdes; Pérez, Ariadna; Martin‐Martin, Gabriel; Facal‐Malvar, Ana; Ferrer, Elena; Pascual, María‐Jesús; Sanz‐Linares, Gabriela; Gago, Beatriz; et al.
Abstract: This is a multicenter prospective observational study that included a large cohort ( n  = 397) of allogeneic (allo‐HSCT; ( n  = 311) and autologous (ASCT) hematopoietic stem cell transplant ( n  = 86) recipients who were monitored for antibody detection within 3–6 weeks after complete severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccination from February 1, 2021, to July 20, 2021. Most patients ( n  = 387, 97.4%) received mRNA‐based vaccines. Most of the recipients (93%) were vaccinated more than 1 year after transplant. Detectable SARS‐CoV‐2‐reactive antibodies were observed in 242 (78%) of allo‐HSCT and in 73 (85%) of ASCT recipients. Multivariate analysis in allo‐HSCT recipients identified lymphopenia < 1 × 10 9 /ml (odds ratio [OR] 0.33, 95% confidence interval [95% CI] 0.16–0.69, p  = .003), active graft versus host disease (GvHD; OR 0.51, 95% CI 0.27–0.98, p  = .04) and vaccination within the first year of transplant (OR 0.3, 95% CI 0.15–0.9, p  = .04) associated with lower antibody detection whereas. In ASCT, non‐Hodgkin's lymphoma (NHL; OR 0.09, 95% CI 0.02–0.44, p  = .003) and active corticosteroid therapy (OR 0.2, 95% CI 0.02–0.87, p  = .03) were associated with lower detection rate. We report an encouraging rate of SARS‐CoV‐2‐reactive antibodies detection in these severe immunocompromised patients. Lymphopenia, GvHD, the timing of vaccine, and NHL and corticosteroids therapy should be considered in allo‐HSCT and ASCT, respectively, to identify candidates for SARS‐CoV‐2 antibodies monitoring.